Subambient daytime cooling enabled by hierarchically architected all-inorganic metapaper with enhanced thermal dissipation. (1st June 2022) - Tian, Yanpei; Liu, Xiaojie; Wang, Ziqi; Li, Jiansheng; Mu, Ying; Zhou, Shiyu; Chen, Fangqi; Minus, Marilyn L.; Xiao, Gang; Zheng, Yi
Abstract: Daytime radiative cooling shows great promise for cooling terrestrial objects without energy consumption. Intensive research has yielded numerous material candidates, such as nanophotonic structures and polymer-dielectric composites, however, challenges exist, ranging from the cost of nanofabrication for nanophotonic structures to environmental threats of micro and nanoplastics during polymer degradation under sunlight exposure. Moreover, the effect of a material's thermal conductivity on heat dissipation has been overlooked in the past. Herein, we report the synthesis and study of a hierarchical hydroxyapatite inorganic radiative cooling (HIRC) metapaper to simultaneously achieve efficient radiative cooling and enhanced thermal dissipation to accelerate heat release. We demonstrate that the HIRC metapaper is featured with high solar reflectance (0.99) and high mid-infrared thermal emittance (0.90) and it yields a subambient temperature drop of 5.1 °C under solar irradiance of 950 W m −2 and a peak radiative cooling power of 104 W m −2 under the solar intensity of 910 W m −2 without polyethylene windshields. Moreover, the thermal conductivity of the metapaper exceeds that of polymer composites, thus enhancing the thermal dissipation from the underlying space. Furthermore, the hydroxyapatite's biocompatibility eliminates the concern of micro and nanoplastics release into the environment. Graphical abstract: Highlights: The enhancement of thermal dissipation on the hierarchical all-inorganic metapaper. The metapaper has a temperature drop of 5.1 °C under solar irradiance of 950 W m −2 . Hierarchically architected hydroxyapatite fiber features solar reflectance of 0.99. The wool-like hydroxyapatite fiber can be scaled by the roll-to-roll industry.